Perencanaan Lingkungan Pendidikan Islam di Sekolah Islamic Boarding School SMK IT Cyber Orenz Leuwiliang - Iim Imaroh; Maemunah Sa’diyah; Khoirul Anam (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
One type of education in Indonesia that deepens on the knowledge of the Islamic religion while also taking part in daily activities within the school environment and for students or students living in dormitories is the Islamic Boarding School. The educational environment in a dormitory or boarding school greatly determines the success of the Islamic education goals that are to be achieved in Islamic boarding schools. For this reason, the Islamic education environment must be planned correctly and appropriately. This research aims to determine the planning of the Islamic education environment of Islamic Boarding School at Senior Vacational high school of IT Cyber Global Orenz located in Leuwiliang, West Java. This research is the descriptive qualitative research. The data collection techniques are observation, interviews and documentation. The results of this research show that the educational environment of Islamic Boarding School at senior vocational highschool of IT Cyber Global Orenz already has environmental characteristics that are in accordance with Islamic education, namely Islamic characteristics, starting from the library environment, places of worship and good learning environments at school. or in the dormitory. Key words: Islamic boarding school, Islamic education environment, Islamic education environment planning.